TINJAUAN BOARD GAME EDUKATIF & NON EDUKATIF - Andrew Suryadi; Edy Muladi (Universitas Mercu Buana, 2021)
The purpose of this research is to research the behavior and experience when playing a board game that shown by people or groups and analyzes whether it's possible to bring the fun experience when playing non-educative board game into the educative board game, so the learning experience can give an unforgettable experience and lessons to be taught through the board game itself. The research method that I used is interview method, observation method, and comparative study method. There is some quality from non-educative board games that can be adapted for the educative board games. From the way they are played, game duration, game transition, victory condition in game, and how the player interacts with each other. Besides giving education value as the main purpose of an educative board game, the way it played actually can adapted also from the non-educative board games, from the fun in playing and the impact of it to whomever that plays it.